Pharmacokinetic, pharmacodynamic, and transcriptomic analysis of chronic levetiracetam treatment in 5XFAD mice: A MODEL‐AD preclinical testing core study. Issue 1 (23rd August 2022) - Onos, Kristen D.; Quinney, Sara K.; Jones, David R.; Masters, Andrea R.; Pandey, Ravi; Keezer, Kelly J.; Biesdorf, Carla; Metzger, Ingrid F.; Meyers, Jill A.; Peters, Johnathon; Persohn, Scott C.; McCarthy, Brian P.; et al.
Abstract: Introduction: Hyperexcitability and epileptiform activity are commonplace in Alzheimer's disease (AD) patients and associated with impaired cognitive function. The anti‐seizure drug levetiracetam (LEV) is currently being evaluated in clinical trials for ability to reduce epileptiform activity and improve cognitive function in AD. The purpose of our studies was to establish a pharmacokinetic/pharmacodynamic (PK/PD) relationship with LEV in an amyloidogenic mouse model of AD to enable predictive preclinical to clinical translation, using the rigorous preclinical testing pipeline of the Model Organism Development and Evaluation for Late‐Onset Alzheimer's Disease Preclinical Testing Core. Methods: A multi‐tier approach was applied that included quality assurance and quality control of the active pharmaceutical ingredient, PK/PD modeling, positron emission tomography/magnetic resonance imaging (PET/MRI), functional outcomes, and transcriptomics. 5XFAD mice were treated chronically with LEV for 3 months at doses in line with those allometrically scaled to the clinical dose range. Results: Pharmacokinetics of LEV demonstrated sex differences in Cmax, AUC0‐∞, and CL/F, and a dose dependence in AUC0‐∞ . After chronic dosing at 10, 30, 56 mg/kg, PET/MRI tracer 18 F‐AV45, and 18 F‐fluorodeoxyglucose ( 18 F‐FDG) showed specific regional differences with treatment. LEV did not significantly improve cognitive outcomes. Transcriptomics performed by nanoString demonstrated drug‐ and dose‐related changes in gene expression relevant to human brain regions and pathways congruent with changes in 18 F‐FDG uptake. Discussion: This study represents the first report of PK/PD assessment of LEV in 5XFAD mice. Overall, these results highlighted non‐linear kinetics based on dose and sex. Plasma concentrations of the 10 mg/kg dose in 5XFAD overlapped with human plasma concentrations used for studies of mild cognitive impairment, while the 30 and 56 mg/kg doses were reflective of doses used to treat seizure activity. Post‐treatment gene expression analysis demonstrated LEV dose‐related changes in immune function and neuronal‐signaling pathways relevant to human AD, and aligned with regional 18 F‐FDG uptake. Overall, this study highlights the importance of PK/PD relationships in preclinical studies to inform clinical study design. Highlights: Significant sex differences in pharmacokinetics of levetiracetam were observed in 5XFAD mice. Plasma concentrations of 10 mg/kg levetiracetam dose in 5XFAD overlapped with human plasma concentration used in the clinic. Drug‐ and dose‐related differences in gene expression relevant to human brain regions and pathways were also similar to brain region–specific changes in 18F‐fluorodeoxyglucose uptake.